Utilization Of Coconut Water Post Covid-19 Vaccine For Students Of West Bilah State 5 junior high school - Rodiah Pasaribu; Pristiyono Pristiyono; Yudi Prayoga; Marlina Siregar (International Journal Of Community Service, 2022)
Corona virus (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Most people who contract COVID-19 will experience mild to moderate symptoms, and will recover without special treatment. However, some people will experience severe pain and require medical assistance. The spread of this virus also has an impact on health that occurs through the mouth or nose of an infected person through small fluid particles when the person coughs, sneezes, talks, sings, or breathes.The Covid-19 vaccine is a biological product that contains antigens in the form of microorganisms or part of the resulting substance which is processed in such a way that it is safe, which when given to a person will cause active specific immunity. The Indonesian government's efforts in dealing with the Covid-19 problem aim to create herd immunityso that people become more productive in carrying out their activities. Coconut water is a clear liquid tapped from young, green coconuts, which contains several nutrients and electrolytes. More than 95% of coconut content is water. In the implementation of community service, the method used is socialization by explaining material about Covid-19, Utilization of coconut water, vaccines, various types of vaccines. The implementation of these activities was explained with the help of power points and the distribution of questionnaires.